Activation of human smooth muscle BK channels by hydrochlorothiazide requires cell integrity and the presence of BK β1 subunit - MARTÍN Pedro; MONCADA Melisa; KUNTAMALLAPPANAVAR Guruprasad; DOPICO Alex M; MILESI Verónica (Acta Pharmacologica Sinica, 2018)
Abstract Thiazide-like diuretics are the most commonly used drugs to treat arterial hypertension, with their efficacy being linked to their chronic vasodilatory effect. Previous studies suggest that activation of the large conductance voltage- and Ca2+-dependent K+ (BK) channel (Slo 1, MaxiK channel) is responsible for the thiazide-induced vasodilatory effect. But the direct electrophysiological evidence supporting this claim is lacking. BK channels can be associated with one small accessory β-subunit (β1–β4) that confers specific biophysical and pharmacological characteristics to the current phenotype. The β1-subunit is primarily expressed in smooth muscle cells (SMCs). In this study we investigated the effect of hydrochlorothiazide (HCTZ) on BK channel activity in native SMCs from human umbilical artery (HUASMCs) and HEK293T cells expressing the BK channel (with and without the β1-subunit). Bath application of HCTZ (10 μmol/L) significantly augmented the BK current in HUASMCs when recorded using the whole-cell configurations, but it did not affect the unitary conductance and open probability of the BK channel in HUASMCs evaluated in the inside-out configuration, suggesting an indirect mechanism requiring cell integrity. In HEK293T cells expressing BK channels, HCTZ-augmented BK channel activity was only observed when the β1-subunit was co-expressed, being concentration-dependent with an EC50 of 28.4 μmol/L, whereas membrane potential did not influence the concentration relationship. Moreover, HCTZ did not affect the BK channel current in HEK293T cells evaluated in the inside-out configuration, but significantly increases the open probability in the cell-attached configuration. Our data demonstrate that a β1-subunit-dependent mechanism that requires SMC integrity leads to HCTZ-induced BK channel activation.